Pergumulan Politik Hukum Perkawinan Islam Dan Adat Di Indonesia - Kamsi, Kamsi (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2012)
The  establishment  of  the  law  should  not  be  in  a vacuum  but rather  cultural  particularities  of the community  with their  cultural roots.  Because the law  in the service of  society,  the legal  system  must  also  trademark  the  same  cultural  roots communities it serves. Therefore,  it  becomes inevitable  that the political vision of  making  the  culture of  the community  and the interests  of  different  political,  economic,  social,  cultural (poleksosbud)  is  a  parallel  society.  Accordingly,  periodically  in line  with  the  historical  appearance  of  terms  of  customary  law, then  the  exposure  will  be  described  in  periodically.  First  is  the forms of  the  Dutch  government's policy  towards  the Islamic law and custom.  It  is important to  understand the different  kinds of consequences caused by  the policies of  the colonial  legal system. While  the  second  part  of  the  discussion  is  the  relationship between  Islamic  law  and  custom  in  the  independence  of Indonesia,  so  that  an  image  between  the  two  legal  systems  is obvious.